1988
DOI: 10.1073/pnas.85.8.2633
|View full text |Cite
|
Sign up to set email alerts
|

The lethal myospheroid gene of Drosophila encodes a membrane protein homologous to vertebrate integrin beta subunits.

Abstract: A mutant of Drosophila melanogaster carrying the lethal(l) myospheroid mutation [l(1)mys] has a defective musculature and a phenotype that suggests a defect of basement membranes. The genomic region that is interrupted by an insertion in a mutant carrying l(l)mys was used to isolate cDNA clones, and their sequences are presented here. The cDNA sequence predicts a cysteine-rich integral membrane protein that displays 45% sequence identity to chicken integrin and the human fibronectin receptor (3 subunit and muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(103 citation statements)
references
References 33 publications
3
99
0
1
Order By: Relevance
“…The role of integrins in various biological processes has been elucidated either by truncation/mutation of the sequences of the receptor or by interference in its functional (MacKrell et al, 1988). The [31-related RGD-blocking peptides have been shown to perturb mesencephalic neural crest migration (Boucaut et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The role of integrins in various biological processes has been elucidated either by truncation/mutation of the sequences of the receptor or by interference in its functional (MacKrell et al, 1988). The [31-related RGD-blocking peptides have been shown to perturb mesencephalic neural crest migration (Boucaut et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…2C,D), allowing any enhancement of rotational defects to be easily recognised. Halving the dose of α-laminin [wing blister (Martin et al, 1999)] and the integrin β subunit [myospheroid (MacKrell et al, 1988)] did not modify the Star/+ phenotype. In contrast, alleles of E-cadherin [shotgun (Tepass et al, 1996)] showed a significant interaction with Star, with many more misrotated ommatidia (Fig.…”
Section: Cadherin-based Adhesion Is Involved In Rotationmentioning
confidence: 99%
“…(Harden et al 1996;Lotz et al 1997Lotz et al , 2000Stark et al 1997;Goldfinger et al 1999;Mercurio et al 2001). For example, mutations in the Drosophila integrin receptor ␤-subunit (myospheroid) and in the ␣3 subunit (scab) of the integrin receptor lead to a DC defect (MacKrell et al 1988;Stark et al 1997).…”
Section: Dorsal Closure In Drosophila As a Model System For Wound Repairmentioning
confidence: 99%